(untitled) (Bangladesh Journal of Public Administration, 2023)
The insightful understanding of the recruitment and selection process of civil servants in Bangladesh is crucial as it manifests the idiosyncratic nature of civil service in enrolling the talents in the highest echelon. The modern civil service system in Bangladesh is influenced by three pressing traditional legacies: Colonial Legacy, Pakistan Legacy, and Post-Independence Legacy. In the past, recruitment and selection in civil service exemplify as apolitical and elitist. Max Weber’s prescriptions for neutral, permanent, talented, and salaried public officials assumed almost a universal acceptance. Public Service Commissions were established to select and induct meritorious recruits. However, over the years, the apolitical and the elitist nature of civil service has been disintegrated due to political polarization and embedded culture of clientelism. The invasion of politics and option for a representative bureaucracy resulted in the formulation of various types of quotas for some groups which made a serious dent in the concept of merit. The experience of last fifty years suggests that traditional examination system and the recruitment of all cadres through the same examination, effects of quota system, interference of political forces and corruption has damaged the efficiency of the civil service. The civil service system in Bangladesh is currently afflicted by ‘Gresham’s Law Syndrome’ (where the bad drives out the good), ‘Humpy Dumpty Disorder’ (design flaw and wrong staffing) and ‘Isomorphic Mimicry’ (which look like modern institutions on paper but prove to be ineffective) which creates an unsuited administrative structure delineated as maladministration. A robust recruitment and selection system is imperative for enlistment of flair and professionals within the service for institutional effectiveness. Against this backdrop, this paper briefly reviews the merit versus representation debate, the policy and process of recruitment and selection, the examination system, and the role of the Bangladesh Public Service Commission (BPSC), (shortly referred to as PSC) as a recruiting agency, followed by a discussion on the consequences of political pressure placed on the PSC, based on secondary data and content analysis.